Peacekeeping Strategies and the Role of Rwanda in the Conflict in the Democratic Republic of the Congo - Svetlana A. Bokeriya; Manasa Mahapa; Anita Kiamba (Vestnik RUDN. International Relations)
The relevance of the research topic stems from the need to examine the role and place of Rwanda in the internal political conflict in the Democratic Republic of the Congo (DRC) to further improve the effectiveness of peacekeeping efforts in resource and ethnic conflicts. The article aims to identify Rwanda’s role in the ongoing conflict in the DRC and to evaluate the extent to which its actions have impeded the effectiveness of peacekeeping efforts in the country. The study examines the strategies used by Rwanda in the DRC, including support for armed rebel groups, illegal mining of natural resources, and their impact on the dynamics of the conflict. The authors conclude by emphasizing the need for international intervention and cooperation to address the complex conflict dynamics in the DRC, as well as to help boost peacekeeping efforts of the various parties. Despite the implementation of numerous peacekeeping initiatives since the Second Congolese War to improve relations between the DRC and Rwanda, tensions continue to rise. The principal findings of the study are that Rwanda is involved in the DRC’s continued conflict and exploiting the latter’s internal political instability to plunder Congolese resources, as well as acting as a conduit for the smuggling of the DRC resources destined for Asian, Middle Eastern and Western countries. In conclusion, the authors posit that the conflict should be resolved through diplomatic methods involving the great powers and the African Union (AU). The paper employs a comprehensive approach to the processes and phenomena under consideration and uses the principle of critical evaluation of information. The theoretical and methodological basis of the research is offensive realism, which takes into account the desire of states to solve their national security issues first and foremost, even at the expense of their partnership relations with other international actors.